Financing Practices and Preference of Small and Medium Construction Firms in Ghana - Alex Kojo Eyiah; Francis Kwesi Bondinuba (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
This study is based on the premise that a better understanding of the sources of financing, the financing practices and preference of small and medium scale construction firms (SMCFs) will help promote the growth and competitiveness of small and medium enterprises (SMEs). Survey methods were adopted, with 400 questionnaires administered to SMCFs, and 48 per cent response rate was obtained. The findings show that most SMCFs raised finance for the purchase of construction materials, payment of wages and purchase of plant and equipment. The three most important source of finance were in the order of overdraft facilities, credits from materials suppliers and relatives and friends. However, the three most preferred sources of finance, if readily available, were in the order banks loans, plant hiring organizations support and mobilization payments from client. The study makes a specific contribution in the context of effort finding solutions to address the financing challenges of SMCFs in Ghana. This would be of significant value to researchers, entrepreneurs in the construction sector, policy makers and donors interested in the SME sector development.